Historical Development of Thematic Interpretation of al-Qur’an - Eni Zulaiha; Anindita Ahadah; Andi Malaka (UIN Sunan Gunung Djati Bandung, 2021)
The discussion on the definition of thematic (maudu’i) interpretation or what is commonly called thematic interpretation is a product of interpretation that solves every existing problem. The periodization of the development of maudu’i interpretation is also an important thing that must be known and understood both among the academics of the interpretation of science and the general public. Especially among commentators, because by knowing the periodization, academics can find out the characteristics of the interpretation. There are still few articles that discuss the periodicity of maudu’i interpretations; therefore in this article, the author will discuss the development of maudu’i interpretations from time to time, where the forerunner of Maudu’i interpretations has existed since the time of the prophet. Still, Maudu’i interpretations that have been neatly arranged as new methodologies have been formed recently. Among the periods to be discussed are: Prophet Muhammad's Period, Classical/Mutaqaddimin Period (1-2 H / 6-7 AD), Medieval Period (3-9H/9-15M), and Modern-Contemporary Period (12th Century AD). 14H / 18-21 AD). What makes the difference in the development of maudu’i interpretation of the four phases is the methodology. More recently the science of interpretation is also growing, including maudu’i interpretation.